Incorporating discrete choice experiments into long-term care insurance policy decisions: evidence from China - Chen, Qian; Dong, Yuting; Lyu, Xinyue (Frontiers in Public Health, 2025)
BackgroundRapid population aging has prompted most emerging economies to consider introducing long-term care insurance (LTCI) as part of a comprehensive social health protection scheme. China is also in the process of establishing its own LTCI framework. However, the details of the scheme are still being explored in pilot cities, and a long-term solution has yet to be finalized. This study aims to examine the insurance preferences of potential enrollees, providing insights to inform further adjustments to the existing framework.MethodsWe examine discrete choice experiment (DCE) evidence from LTCI and evaluate several relevant attributes, including the elimination period, maximum monthly benefit, out-of-pocket rate, and annual premium. The study uses a mixed logit model to elicit respondents’ preferences and willingness to pay (WTP) for these attributes of LTCI and uses physical health status to assess heterogeneity in responses to insurance choice.ResultsWe found that most respondents would consider purchasing LTCI, with respondents most preferring the following attributes: (1) an out-of-pocket rate of 25%, (2) a maximum monthly benefit level of 2000 CNY (about 296 USD), and (3) a three-month elimination period. In addition, among the control variables, marital status, personal self-rated health, and the number of children were significant to varying degrees.ConclusionThe study can provide a reference for further adjustments to the existing scheme, increasing residents’ willingness to participate in insurance and promoting the sustainable development of long-term care insurance.